2003
DOI: 10.1255/jnirs.358
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Models Based on NIR Spectra for Sugar Content Prediction in Apples

Abstract: The sugar content of Golden Delicious apples is predicted using near infrared (NIR) spectrometry. The study focuses on the metrological characteristics of the sugar content measurement and external parameters involved in the lack of robustness of the NIR-based model. The external parameters were fruit temperature, spectrometer temperature and ambient light. The first two factors influenced the prediction accuracy: (i) a fruit temperature variation altered the prediction, the relationship seems to be described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 8 publications
(14 reference statements)
1
12
0
2
Order By: Relevance
“…The 830-920nm spectral window, corresponding to the sugar absorbance peaks [22], was removed to avoid the concomitant influence of the major chemical constituent in grapes. For portable application test, only a few wavelengths were selected.…”
Section: Methodsmentioning
confidence: 99%
“…The 830-920nm spectral window, corresponding to the sugar absorbance peaks [22], was removed to avoid the concomitant influence of the major chemical constituent in grapes. For portable application test, only a few wavelengths were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Both reports concluded that if the calibration model was developed with sample temperatures covering the range of future sample temperatures, then prediction accuracy was high. Sanchez et al (2003) also noted that the influence of spectrometer and fruit (apple) temperature was mainly on bias, not RMSEP(C). However, the effect of spectrometer temperature on bias was more than twice that of fruit temperature.…”
Section: Introductionmentioning
confidence: 95%
“…Recent research on the use of near‐infrared spectroscopy (NIRS) on apples has focused on determining the soluble solids content, firmness and acidity . However, these are not the only quality attributes of relevance in apples.…”
Section: Introductionmentioning
confidence: 99%